The Influence of Informal Economy, Corruption, and Economic Freedom on Tax Revenue (Case Study: 35 World Countries, Period 2000-2020) - Herza Hendradijaya; Marselina Djayasinga (International Journal of Economics, Management and Accounting (IJEMA), 2024)
A nation's economy now plays a significant role in its overall growth. A dependable source of money is necessary for the nation to have a robust and stable economy, and tax revenue is one of the most popular sources. This study tries to ascertain how much a nation may optimize its tax income and how far it can go past the issue of moral hazard behavior, which has the potential to destabilize the economy. Tax revenue, the informal economy, the corruption perception index, and economic freedom are the variables that were employed in this study. The regression model employed in this study is the Fixed Effect Model. The findings show that economic freedom and the informal economy have a negative and significant impact on tax revenue, while the corruption perception index variable has a positive and significant impact.